Effect of X‐ray spot size on liquid jet photoelectron spectroscopy. (30th September 2015) - Olivieri, Giorgia; Goel, Alok; Kleibert, Armin; Brown, Matthew A.
Abstract : A 30 µm pinhole is introduced in the intermediate focus of the SIM beamline at the Swiss Light Source to improve the spot size at the second downstream focus, which is used here for liquid jet X‐ray photoelectron spectroscopy experiments. The 30 µm pinhole reduces the beam dimensions from 250 (v) × 100 (h) µm to 75 × 45 µm for a vertical exit slit of 100 µm. The smaller X‐ray spot results in a substantial decrease in the gas‐phase contribution of the spectra from 40% down to 20% and will help to simplify the interpretation and peak assignments of future experiments.